2020
DOI: 10.1021/acs.jmedchem.0c00255
|View full text |Cite
|
Sign up to set email alerts
|

A γ-Lactam Siderophore Antibiotic Effective against Multidrug-Resistant Gram-Negative Bacilli

Abstract: Treatment of multidrug-resistant Gram-negative bacterial pathogens represents a critical clinical need. Here, we report a novel γ-lactam pyrazolidinone that targets penicillin-binding proteins (PBPs) and incorporates a siderophore moiety to facilitate uptake into the periplasm. The MIC values of γ-lactam YU253434, 1, are reported along with the finding that 1 is resistant to hydrolysis by all four classes of β-lactamases. The druglike characteristics and mouse PK data are described along with the X-ray crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…It is common for the MICs of THAs to be determined against bacteria grown in both iron‐limited and iron‐sufficient conditions (Figure 5A). As iron uptake pathways are upregulated in response to iron limitation, an inverse correlation between iron concentration and antibacterial activity is often used to infer the utilisation of siderophore transport pathways by THA candidates [11,14–21] . A recent example can be found in work by Goldberg et al .…”
Section: Iron‐dependent Antibacterial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…It is common for the MICs of THAs to be determined against bacteria grown in both iron‐limited and iron‐sufficient conditions (Figure 5A). As iron uptake pathways are upregulated in response to iron limitation, an inverse correlation between iron concentration and antibacterial activity is often used to infer the utilisation of siderophore transport pathways by THA candidates [11,14–21] . A recent example can be found in work by Goldberg et al .…”
Section: Iron‐dependent Antibacterial Activitymentioning
confidence: 99%
“…in the development of a γ‐lactam‐monocatechol conjugate, YU253434 (Figure 7). [18] After observing encouraging potencies against Pseudomonas aeruginosa PAO1, the MIC of YU253434 was re‐determined in iron‐limited MHII at various concentrations of supplemented iron(III) chloride. Encouragingly, the MIC increased with iron concentration in a similar fashion to the known THA cefiderocol, suggesting siderophore‐mediated uptake into the periplasm (Table 1), whereas no MIC change was observed for control compound ceftazidime (Figure 7).…”
Section: Iron‐dependent Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach takes advantage of P. aeruginosa ’s own virulence factor. In that respect, a γ-lactam was conjugated to a siderophore moiety, taking advantage of the intrinsic siderophore uptake mechanism of P. aeruginosa [ 70 ]. These creative and effective strategies in combating emerging broad-spectrum resistance demonstrate that only continuing research and effort lead to novel antimicrobials eventually overcoming the multidrug resistance of P. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%
“…The concept of using the siderophore importers present in Gram-negative bacteria to facilitate the intake of antibiotics into the periplasmic space [50] has been applied to the development of a new compound endowed with interesting activity against multidrug-resistant (MDR) bacteria. Goldberg et al [51] have reported the design, synthesis, structural characterization and antimicrobial activity of a novel pyrazolidinone antibiotic containing a dihydroxyphthalimide siderophore mimetic. The compound, dubbed YU253434, contains the 2-(2-aminothiazol-4-yl)-2-(2-carboxypropan-2-yloxyimino)acetamido moiety of ceftazidime linked to the pyrazolidinone nucleus, which in turn bears a dihydroxyphtalimide acting as a siderophore mimic (Figure 10).…”
Section: Highlighted By Stefano Manganimentioning
confidence: 99%